Tender process of the Putrajaya 8MD3-infrastructure development package - Mohd Yazid, Nabihah (Universiti Teknologi MARA, Perak, 2022)
Tender process seems to be very important because it provides an effective way for companies to examine whether they have the best supplier available for their specific needs, while also not prohibiting the reappointment of the incumbent supplier should that company be exclusive and out the best available to provide the services required. Tendering also an important stage because it must be completed properly in order for the company to win a bid, receive a letter of award, and accomplish the tender project. Therefore, this report will discuss about the tendering strategies.